Correlation between Scattering Matrix, Return Loss and Interface Reflection Loss in Nicolson Rose Wear Approximation - Wakid Ali Muntoha; Adam Badra Cahaya; Azwar Manaf (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
The phenomenon behind the absorption of electromagnetic waves by absorbingmaterials is resonance phenomenon. When there is a similarity between the value of theimpedance of electromagnetic waves in the air and the impedance of the material, theabsorption of energy by the material is maximized. The phenomenon is measured using anauxiliary instrument, namely the Vector Network Analyzer. This instrument is very effective forcalculating the absorption value of electromagnetic waves. However, the Vector NetworkAnalyzer instrument which is mostly available in Indonesian research institutions cannot directlydisplay the reflection loss of the electromagnetic wave absorbing material. An effective methodthat is effective for calculating the absorption in electromagnetic wave absorbing material isNicolson Rose Wear method. In this article, we design a computational tool based on NicolsonRose Wear approximation to calculate the reflection loss values from scattering matrix andcomparing it with return loss, which is often mistook as reflection loss.